Hubungan Sosial Peserta Didik Berbakat Intelektual dengan Teman Sebaya di Kelas X SMA Negeri 7 Padang - Heni, Tatis Febri; Helma, Helma; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
This research is purposed to describe social relationship of intellectually gifted students with their peers in tenth grafe class of SMA N 7 Padang. It was analyzed from: 1) Associative, such as : teamwork, accommodation and assimilation. 2) Dissociative, such as: competition, conflict and controversy. This research is descriptive research which describes real condition. Moreover, the population of this research is eleventh grade students of SMA N 7 Padang. Then, sample was taken by using total purposive sampling. It was 24 students . in addition, an instrumentation of research was questionnaire. Meanwhile, data analysis used percentage technique. According to research findings, it shown that the social relationship among students were not good enough it can be seen from each indicator. Furthermore, the cooperation of studentsâ social relationship was categorized good enough, it was 45,83% then, acomomodation or deal was categorized good enough, it was 41,67% Next, assimilation or socialize ability was not good enough 62,5%, social relationship associated with competition or rivalry was categorized good enough 58,33% moreover, conflict was not good enough 87,5% and controversy was not good enough 45,83% from respondents. Based on findings recapitulation, it can be said that all students filled the questionnaire who shown that all social relationship of intelactually gipted students with their peers in tenth grade class SMA N 7 Padang was categorized good enough.